The determinants of money demand in China - Xiangsheng Dou (Cogent Economics & Finance, 2018)
Money demand and its stability have a great impact on the economy of a country. Because China's financial and monetary system has been in reform, there are many uncertainties in money demand. Especially, China's money demand has its own particularity. This paper studies the determinants of China's money demand through building a linear econometric model and SVAR model. The empirical results show that China's money demand is mainly decided by income, interest rate and expected inflation rate. However, other factors, such as financial innovation, government debt, capital mobility and currency substitution, play a relatively small role, mainly because China's financial and monetary system has been under reform. The regression results of sample data from different periods show that money demand in China is unstable, indicating that China's macro-economy has certain risks. This finding suggests that China should adopt prudent financial and monetary policies to cope with the uncertainty of money demand in the future.
Keywords: 330; money demand; money demand determinants; monetary policy